Extrato de sumagre (Rhus coriaria): propriedades bioativas e encapsulação para aplicação em cookies - Santos, Adriely Cristina dos (2024)
Sumac (Rhus coriaria) is a plant rich in flavonoids, tannins, polyphenolic compounds and organic acids. In addition to its health benefits, this plant has antioxidant and antimicrobial properties, which gives it great potential in replacing chemical preservatives. In this sense, the present work aimed to evaluate the physicochemical, technological and bioactive properties of cookies added with sumac extract, both in free form and encapsulated in polyvinylpyrrolidone (PVP). Spreadability, mass loss, objective color, water activity, proximate composition, instrumental texture, antioxidant activity, total phenolics, and lipid oxidation were determined. Three cookie formulations were prepared: control (C), with the addition of the extract in free form (L), and with the addition of the encapsulated extract (E). Regarding color, it was observed that the samples with the encapsulated extract showed greater red color intensity, with a chromatic a* value of 11.24 (C = 4.29 and L = 6.09), and lower values for the luminous intensity, presenting L* of 52.36 (C = 69.73 and L = 61.73). Water activity differed between samples, being lower (wa = 0.39) for cookies with encapsulated extract (E). Cookies with the addition of encapsulated extract (E) had the highest moisture content (10.10%). The highest value of antioxidant activity was from the treatment with encapsulated extract (E), with 47.56%, with only the control differing from the others. The treatment with free extract (L) presented the highest value of phenolic compounds (6.89 mg GAE g⁻¹), differing from the control (C) and the encapsulated extract (E). The puncture force was statistically different for the three treatments, with the greatest bending force being the treatment with free extract (L), with 16.82 N, which differs from the control treatment but does not differ from the treatment with encapsulated extract. Sumac extract has an antioxidant effect and phenolic compounds in its composition, demonstrating potential for application as a natural additive in industry, helping with the shelf life of foods.